Being held to account: Detainees' perceptions of police body-worn cameras. Issue 2 (June 2019) - Lee, Murray; Taylor, Emmeline; Willis, Matthew
Police organisations across the world are embracing body-worn video camera technology. The justification for this is to enhance public trust in police, provide transparency in policing activity, increase police accountability, reduce conflict between police and public, and to provide a police perspective of incidents and events. However, while the corpus of research into the efficacy and operational practicalities of police use of body-worn video cameras is developing, questions on some elements of their impact remain. The majority of scholarship has hitherto been evaluations focused on the impact of the cameras on police use of force and on the numbers of complaints against the police. Alternatively, this article explores body-worn video cameras from the perspective of police detainees, and specifically, detainees' perceptions of the capacities of body-worn video cameras to deliver promised increased levels of accountability in policing. The article draws on a survey and research interviews with 907 police detainees across four Australian jurisdictions. While respondents largely support the use of body-worn video cameras they also identify a number of caveats. We conclude by suggesting that there are still impediments in body-worn video cameras to achieving the level of accountability promised by advocates and expected by the respondents.